Cover Image. Issue 6 (6th October 2018) - Feiner, Nathalie; Rago, Alfredo; While, Geoffrey M.; Uller, Tobias
Abstract : ON THE COVER: The cover image, by Nathalie Feiner et al., is based on the Research Article Developmental plasticity in reptitles: Insights from temperature‐dependent gene expression in wall lizard embryos, DOI:10.1002/jez.2175 .